Klasy eksperymentalne w szkołach powszechnych w Wilnie w okresie dwudziestolecia międzywojennego - Pękowska , Marzena (Studia Edukacyjne, 2023)
The interwar period was characterized by an experimental movement in the field of educational methods. This movement was the result of postulates announced as part of the new education trend, stimulating an alternative and innovative approach to the didactic and educational work of the school. The publication presents the organization of teaching in experimental classes in elementary schools No. 22 and No. 7 in Vilnius in the years 1918-1939. School inspectors’ reports collected in Lithuanian Central State Archives in Vilnius were mainly used for this purpose.